The Social Reality Behind a 1996-Street-Riot - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
This work is an attempt to analyze-through conventional as well as ethno-methodological and phenomenological methods of Sociology-the social facts behind a youth riot on a labor day, in Istanbul, in 1996, wherein life and property losses occurred. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Social reality; riot; violence; shanty towns